2004
DOI: 10.1111/j.1365-2656.2004.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for sugars and amino acids and their conditionality in a diverse nectar‐feeding ant community

Abstract: Summary1. Feeding preferences of nectarivorous ants for sugars and amino acids were studied in an Australian tropical rain forest using artificial nectar solutions. Fifty-one ant species were recorded feeding on the solutions. 2. Preferences among carbohydrates were principally concordant between ant species. In paired tests, sucrose was often preferred over fructose, glucose, maltose, melezitose, raffinose and xylose, respectively. Attractiveness of sucrose baits increased with concentration. 3. Many ant spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
161
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(175 citation statements)
references
References 63 publications
(130 reference statements)
8
161
2
4
Order By: Relevance
“…For example, in the Australian rainforests, Technomyrmex sp. (identified as albipes, but likely to be dificilis based on Bolton 2007) prefers some sugars over others and solutions containing amino acids to those with just sugars (Blüthgen and Fiedler 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the Australian rainforests, Technomyrmex sp. (identified as albipes, but likely to be dificilis based on Bolton 2007) prefers some sugars over others and solutions containing amino acids to those with just sugars (Blüthgen and Fiedler 2004).…”
Section: Discussionmentioning
confidence: 99%
“…8% fructose and 6% glucose in the 20% solution and 31% fructose and 25% glucose in the 80% solution) and small (mean = 0.053 g) and large (mean = 0.36 g) crickets. The sugars found in clover honey, glucose, and fructose are the main components of the honeydew and nectars exploited in natural communities (Blüthgen & Fiedler, 2004;Woodring et al, 2004) and the concentrations we used fall towards the ends of the spectrum found in nature (Blüthgen & Fiedler, 2004). The crickets were representative of the proteinaceous resources frequently exploited by ants.…”
Section: Experimental Designmentioning
confidence: 99%
“…Ricks & Vinson (1970) found that Solenopsis saevissima richteri Forel (Hymenoptera: Formicidae) and S. invicta preferred sucrose over xylose, ribose, mannose, arabinose, and galactose. Sucrose was also often preferred by Anonychomyrma gilberti (Forel), Technomyrmex albipes (Smith), and Camponotus vitreus (Smith) (Hymenoptera: Formicidae) (Blüthgen & Fiedler 2004), whereas melezitose was preferred by several ant species and is important for ant-aphid relationships (Kiss 1981;Maurizio 1985;Völkl et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Lasius niger (L.) (Hymenoptera: Formicidae) workers preferred trisaccharides over disaccharides and monosaccharides when these sugars were offered in choice tests, and melezitose was the most effective in attracting ants (Völkl et al 1999). Previous studies also showed that the red imported fire ant, Solenopsis invicta Buren (Hymenoptera: Formicidae), had a specific preference for melezitose in laboratory and field tests (Zhou et al 2015), whereas it often preferred sucrose over fructose, glucose, maltose, melezitose, raffinose, and xylose in paired tests (Blüthgen & Fiedler 2004).…”
Section: Introductionmentioning
confidence: 98%